Adaptation and Validation of the Beck Anxiety Inventory in Young Peruvians - Leonardo Gomez, Jherson (2023)
Introduction: Anxiety is a disease that generates restlessness and excessive worry about something threatening, this condition causes disorder for those who suffer from it. A theoretical postulate is Beck’s theory of anxiety (Beck et al., 1999). In Peru there are various figures of population groups that suffer from this disease, but there are no studies of adapted questionnaires that measure anxiety, which are unreliable in a national context. Faced with this, this inventory is a good option that meets the needs to measure the symptomatology of this condition. Objective: Adapt the Beck anxiety inventory in young Peruvians. Method: Psychometric type and instrumental design. Results: In the validity based on the internal structure of the instrument, in the CFA (χ2/df = 3.82; CFI = .98; SRMR = .03; RMSEA = .07); in terms of validity based on the relationship with other variables (r = .84; p < .001; r2 = .70), and on the reliability of the scale (α = .95), which means that the test presents good level of internal consistency. Conclusions: The test presents acceptable evidence of validity and reliability to measure the variable.